Association of metabolic syndrome with oral and systemic conditions in morbidly obese patients - Foratori-Junior, Gerson Aparecido; de Andrade, Francisco Juliherme Pires; Mosquim, Victor; Peres, Matheus de Carvalho Sales; Chaim, Elinton Adami; Peres, Silvia Helena de Carvalho Sales (Universidade Estadual de Campinas, 2019)
Aim: This study aimed to evaluate oral and systemic conditions in morbidly obese patients with and without metabolic syndrome (MS) prior to bariatric surgery. Methods: One hundred patients were included and equally divided into two groups: G1 - with MS (n = 50) and G2 - without MS (n = 50). MS was diagnosed in patients presenting at least three of five signs: abdominal obesity, high triglyceride level, low high-density lipoprotein cholesterol (HDL-C) level, hypertension, and altered fasting glycemia. Variables analyzed included the patients' age, sex, body mass index (BMI), waist-to-hip ratio (WHR), and number of missing teeth. Both BMI and WHR were used to evaluate the risk of developing cardiovascular disease (RCVD). Mann-Whitney, Chi-squared, t test, hierarchical multiple linear regression and binary logistic regression models were used in statistical analyses (p < 0.05). Results: There were no group-wise differences in sex (p=0.631) and BMI (p=0.200); however, the WHR (p=0.009), age (p=0.0001), and number of missing teeth (p=0.0003) were higher in G1. Obese patients with MS who were candidates for bariatric surgery presented higher RCVD than obese patients without MS (p=0.019). Binary logistic regression revealed patient age [adjusted OR=1.05, 95% CI=1.00-1.11, p=0.042] and number of missing teeth [adjusted OR=1.17, 95% CI=1.04-1.31, p=0.013] to be significant predictors of MS. Conclusion: Morbidly obese patients with MS had worse oral and systemic conditions than those without MS, regarding WHR, RCDV and number of missing teeth.
Keywords: Cardiovascular diseases; Metabolic syndrome; Obesity; Tooth loss